Microstructural characterization and mechanical properties of Al-Si-Cu alloys processed by equal channel angular pressing - Nurul Naili Mohamad Ishak (2019)
Recent years, severe plastic deformation (SPD) is recognized as a main technique to produce an ultrafine grained (UFG) structure of aluminium alloys. The most popular and widely applied is equal channel angular pressing (ECAP) technique. Typically, aluminium alloy with dendritic structure is used as feedstock material for ECAP processing. Therefore, in this research a feedstock with a non-dendritic microstructure is preferred to be used in ECAP processing due to the advantage of a good distribution of phase elements in the sample thus increase the mechanical properties of the alloys. The objective of this study is to produce a non-dendritic microstructure feedstock for ECAP process by using cooling slope casting. This study also investigates the evolution of α-Al microstructure, mechanical properties and wear properties of Al-Si-Cu alloys processed by ECAP and to study the effect of T6 heat treatment on α-Al microstructure, mechanical properties and wear properties of Al-Si-Cu alloys. ECAP process were performed by pressing a sample through a 120° die via route A at room temperature. The microstructure of the processed alloys were observed under optical microscope (OM) and scanning electron microscope (SEM) while the mechanical properties of the alloy were validated by Vickers hardness and tensile testing. Sliding wear test was applied to study the wear properties of the alloys. The results obtained indicates that the microstructure features were improves after two ECAP passes as the grain size was obviously refined to 37µm from 75µm in cooling slope cast sample. The hardness and tensile strength of the alloy increased as high as 84.3HV and 237.58MPa after two ECAP passes, compared to the conventional cast alloy with value of 44.6HV and 105.13MPa, respectively. The elongation to fracture decrease from 19% for conventional cast sample, reduce to 12% after processed by ECAP. It was also reveal that the wear resistance of the alloy improved after the combination of cooling slope casting and ECAP process as the volume loss obtained by this sample is lower than other samples with value of 3.3mm3 under 10N applied load. After T6 treatment, the Si particles was seen to be spheroidised in certain region within the globules within the α-Al globules while the other particles such as Cu, Mg and Fe particles were homogeneously dispersed. After T6, the mechanical and wear properties were enhanced as the distribution of particles were more homogeneous. In T6 condition, sample after 2 ECAP passes shows the highest tensile strength with value of 270MPa and the elongation percentage was also increase to 9% from 5%. Volume loss for alloys after T6 was lower than before T6. After 2 ECAP passes, the volume loss decreased to 3.0mm3 under 10N load which indicates better wear properties compared to other samples.